METACOGNITIVE STRATEGY FOR VOCABULARY LEARNING - Jamaris Jamaris (Ta'dib, 2013)
This article proposed some important issues relating with teaching English vocabulary. This article also quoted various literature that have a correaltion with teaching English vocabulary for Indonesian students who were not from English Department. Specially, this article discussed about some issues relating with teaching strategy (Metacognitive strategy) and its procedure in teaching English vocabulary to the students. At last, this article might give a recommendation for those students in improving their English vocabulary.  Key Words: metacognitive  strategy, vocabulary learning